Work, survival and welfare - González, Luis Armando (Teoría y Praxis, 2022)
These notes —which constitute a kind of essay— contain a more or less systematic reflection on the links between work — understood as the expenditure of human energy to obtain resources (energy) to live—, survival —understood as the fundamental requirement that genes make to organisms to ensure their permanence over time—, and well-being — understood as the optimal balance (internal and with the environment) to which organisms tend in their eagerness to survive. The central argument is that human beings, as the “survival machines” that they are, have been (and are) moved by the desire to work less (invest less energy) to obtain more resources (energy) from the environment, a tendency already present in the most rudimentary technologies inherited from other homo species relatives. This energy management in their own favor has resulted in a growing well-being, which has improved their chances of survival, of taking care of themselves and leaving offspring. To support this argument, decisive contributions from evolutionary biology, paleontology and cognitive sciences have been used, mainly following the approaches of Richard Dawkins, Juan Luis Arsuaga, Steven Pinker and Antonio Damasio. Additionally, this article positions itself in a line of natural scientific foundation of the Social Sciences, promoted by the Castro Nogueira team (Laureano, Luis and Miguel Ángel), which questions fundamental theses of the Standard Model of Social Sciences, according to which the social and the cultural can be understood outside the natural (biological, physical, chemical, mental) reality of the human being. In these notes, it is the notions of work and well-being that are examined from these biological, paleontological and neuroscientific criteria.